ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TARIF PAJAK EFEKTIF - Yanuar Nanok Soenarno (Jurnal Akuntansi Bisnis, 2018)
This research wanted to see whether financial factors such as profitability, leverage, liquidity, market share and cash flow affects the company in paying taxes. This study uses all non-financial companies listed on the Indonesia Stock Exchange listing in 2012. From this research resulted that profitability, leverage and liquidity factors affect the level of corporate tax payments. However, shareholder and cash flow factors whose expectations are influential, have no effect. Tax payment strategies that still rely on tax shield to reduce tax payments, making many companies more borrowed to get the funds. Keywords: efective tax rate, profitability, leverage, liquidity, cash flow, Indonesia stock exchange.